PERSEPSI GENERASI MUDA MINANG TERHADAP PEMELIHARAAN PANTUN ADAT DI KENAGARIAN KAMBANG BARAT - Delpa Delpa (Bajang Institute, 2026)
Traditional pantun is one of the forms of oral literature that has an important position in the social and cultural life of the Minangkabau community. It does not merely function as entertainment or language play, but also serves as a medium for conveying traditional values, ethics, politeness, advice, and cultural identity. However, technological development, changes in social interaction patterns, and the increasing use of digital media have created challenges for the transmission of oral cultural practices among younger generations. This study aims to describe the perceptions of young Minangkabau people toward the preservation of traditional pantun in Kanagarian Kambang Barat. This research employed a qualitative approach with a descriptive method. Data were obtained through in-depth interviews with fewer than ten young informants from Kanagarian Kambang Barat. Data analysis consisted of data reduction, data presentation, conclusion drawing, and source triangulation to ensure data validity. The research focuses on young people's understanding of traditional pantun, its meanings and values, their experiences of listening to or performing traditional pantun, perceptions regarding its sustainability, supporting and inhibiting factors, and appropriate strategies for introducing traditional pantun to younger generations. This research is expected to provide an overview of the position of traditional pantun in the lives of young people and serve as a basis for local communities, traditional leaders, educational institutions, nagari governments, and cultural communities in developing culturally relevant preservation strategies.